Main sanitary problems and needs in Turkish fish farming - Çagirgan H. (The use of veterinary drugs and vaccines in Mediterranean aquaculture, 2009)
Fish diseases are often introduced by the inlet water, purchased eggs and fish, as well as by birds, visitors, transport vehicles and farm equipment or by farm employees themselves. Eggs should be purchased only from disease-free farms and they must be disinfected routinely on arrival. Employees also represent a disease hazard, mainly after making deliveries to other farms. Hands, boots, and vehicle tyres should be disinfected. Equipment should be kept separate for each pond and be disinfected after each use. Duration of disinfection should be sufficient to kill pathogens. Dead fish should be removed and losses must be recorded daily. There can be serious problems with fish purchased from other farms and sea bass/sea bream broodstock caught from the marine environment. Such fish can enter the farm without any health control. Farmers should follow quarantine measures strictly. Good husbandry and vaccination programmes should be applied. Disease maps, certification programmes and regulations must be established.
The Use of Veterinary Drugs and Vaccines in Mediterranean Aquaculture, 2003/05/21-23, Izmir (Turkey)